Accompagner par la recherche le changement des pratiques enseignantes au service de la continuité des apprentissages au cycle 3 - Guillaume Escalié; Pascal Legrain (Éducation et Socialisation)
In the new French school curriculum, the period which overlaps primary and secondary education calls for a change in teaching practices to ensure continuity of pupil’s learning. In synchronic (between disciplines) and diachronic (throughout the period) ways, the regular implementation of the same pedagogical designs can be a vector for stabilizing learning in the transition between primary and secondary school. Grounded on a socio-cultural conception of learning and development processes, this paper reports on a collaborative research which aimed to support primary and secondary school teachers to build and implement innovative cooperative learning environments within classrooms on the foundations of a common model. From a methodological point of view, qualitative and quantitative data have been carried out to examine the impact of this pedagogical approach on the teacher activity and pupils’ psychosocial well-being, respectively. On the one hand, the results underlined the importance of considering the implementation of cooperative arrangements in their dimensions both generic and disciplinary. On the other hand, significant effects of this type of design on pupils' self-determined motivation were observed. Finally, proposals are brought forward to optimize the collaborative research approach and its impact on pupils’ acquisitions.